Serum GPL core antibody levels are associated with disease activity and treatment outcomes in Mycobacterium avium complex lung disease following first line antibiotic treatment. (October 2021) - Fukushima, Kiyoharu; Kitada, Seigo; Matsumoto, Yuki; Komukai, Sho; Kuge, Tomoki; Kawasaki, Takahiro; Matsuki, Takanori; Motooka, Daisuke; Tsujino, Kazuyuki; Miki, Mari; Miki, Keisuke; Nakamura, Shota; et al.
Abstract: Background: No objective serum biomarkers of disease course or treatment outcome of Mycobacterium avium complex lung disease (MAC-LD) presently exist. Serum IgA antibody levels against the glycopeptidolipid (GPL) core have good diagnostic accuracy for MAC-LD. However, their usefulness for monitoring and predicting disease course and outcome of MAC-LD following first-line antibiotic treatment remains unclear. Methods: We conducted a single-center retrospective cohort study to investigate the utility of serial measurements of GPL core IgA antibodies for monitoring disease course in 133 patients with MAC-LD following first-line antibiotic treatment. Results: Patients were classified into treatment failure [n = 46 (34.6%)], recurrence [n = 19 (14.3%)], or treatment success [n = 68 (51.1%)] groups according to bacteriological outcomes after chemotherapy. Pretreatment serum anti-GPL core IgA levels in the treatment success group were similar to those in the treatment failure and recurrence groups ( P = 0.6431 and P = 0.9045, respectively). In the treatment success group, serum anti-GPL core IgA levels were significantly and continuously reduced after initiating antibiotic treatment. No significant reductions in anti-GPL core IgA levels were observed in either the treatment failure or recurrence groups. Reduced levels of GPL core antibodies following antibiotic treatment correlated well with treatment outcomes ( P = 0.0045). Conclusion: In this study, by performing serial measurements, we found that GPL core antibody levels were associated with disease activity and treatment outcomes in patients with MAC-LD. Time course analysis of anti-GPL core IgA levels clearly differentiated between patients who achieved treatment success and those who experienced treatment failure or disease recurrence. Highlights: There are no objective serum biomarkers for Mycobacterium avium complex lung disease (MAC-LD). We conducted a single-center retrospective cohort study to investigate the utility of serial measurements of GPL core IgA antibodies. GPL core antibody levels were associated with MAC-LD disease activity and treatment outcomes.